Biocatalytic degradation of environmental endocrine disruptor chlorobenzene via surfactant-optimized laccase-mediator system - Wang, Dan; Huang, Guifang; Yu, Chunming; Wang, Yawen; Baek, Nawon; Zhu, Ruofei (Frontiers in Bioengineering and Biotechnology, 2024)
The emergence of environmental endocrine disruptor chlorobenzene (CB) in surface water and its potential environmental impacts have attracted serious global attention. It is still very difficult to achieve effective degradation of it by catalytic oxidation process under mild conditions. Here, an optimized method for degrading CB in aqueous solution using Trametes versicolor laccase and surfactant-assisted laccase-mediator (SALM) system was investigated. The use of a Tween 80 surfactant enhanced the solubility of CB and promoted its efficient degradation. Under favorable conditions, the SALM system yielded a degradation efficiency of 43.5% and a dechlorination efficiency of 41.55% for CB (25 mg/L) within 24 h. The possible degradation pathway of CB by this system was speculated by detecting the intermediates produced during the reaction. The outcome of the proliferation assays on MCF-7 human breast cancer cells demonstrated a reduction in the estrogenic activity of the CB solution following treatment with the SALM system. Furthermore, the influence of the quantity and positional variation of chlorine substituents on the degradation process was methodically investigated. Moreover, molecular analyses were employed to study the detailed interaction mechanism between laccase and CB, which revealed that the hydrophobic interaction contributed dominantly to binding process. These findings provide an efficient and environmentally friendly degradation system for the development of purification strategies for halogenated pollutants.